2021
DOI: 10.3389/fimmu.2021.582594
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint-Associated Locations of Diffuse Gliomas Comparing Pediatric With Adult Patients Based on Voxel-Wise Analysis

Abstract: Objective: Pediatric diffuse gliomas (pDGs) are relatively rare and molecularly distinct from pediatric pilocytic astrocytoma and adult DGs. Immunotherapy is a promising therapeutic strategy, requiring a deep understanding of tumor immune profiles. The spatial locations of brain tumors might be related to the molecular profiles. We aimed to analyze the relationship between the immune checkpoint molecules with the locations of DGs comparing pediatric with adult patients.Method: We studied 20 pDGs patients (age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…The associations between intracranial tumor location and immune biomarkers remain unknown so far. In the present study, 89.7% of BM samples were originated from the cerebrum, especially the frontal lobe, which is consistent with the findings by Wang et al 36 Zhang et al reported that low expression of PD‐L1 may be associated with the location of primary diffuse gliomas 37 . Our results also exhibited significantly higher PD‐L1 expression on TCs in BM samples derived from the cerebrum.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The associations between intracranial tumor location and immune biomarkers remain unknown so far. In the present study, 89.7% of BM samples were originated from the cerebrum, especially the frontal lobe, which is consistent with the findings by Wang et al 36 Zhang et al reported that low expression of PD‐L1 may be associated with the location of primary diffuse gliomas 37 . Our results also exhibited significantly higher PD‐L1 expression on TCs in BM samples derived from the cerebrum.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, 89.7% of BM samples were originated from the cerebrum, especially the frontal lobe, which is consistent with the findings by Wang et al 36 Zhang et al reported that low expression of PD-L1 may be associated with the location of primary diffuse gliomas. 37 Our results also exhibited significantly higher PD-L1 expression on TCs in BM samples derived from the cerebrum. In addition, we found that the number and largest diameter of BM lesions were negatively correlated with the percentage of CD8 + T cells and PD-L1 expression on ICs in BM lesions.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, its expression level was remarkably correlated with the infiltration levels as well as the corresponding biomarkers of immune cells mentioned above. And the immunotherapy effect was largely affected by the expression of immune checkpoints 49 , which contributes to various prognosis 50 , 51 . In our study, GLUT1 overexpression significantly correlated with low CD8+ T-cell and CD4+ T-cell infiltration, and its expression was positively related to PD-L1 and negatively related to PD-1 in PAAD.…”
Section: Discussionmentioning
confidence: 99%